Efeitos do impeachment presidencial no value at risk das ações negociadas na bolsa de valores de São Paulo - Oliveira, Franklin Alves de (2018)
In all its history, Brazil was intrinsically marked by innumerable moments of economical and political instability. The impeachment of the ex-president of the Republic Dilma Rousseff is the most recent political fact that flourished a considerable amount of turbulence on the country’s economy. The lack of knowledge of the total effects of this process on the financial markets coupled with the great number of informal evidences on the media speculating the possible effects of this event - especially on stock markets - gives rise to the suspicion that the change in investor’s perception vis-à-vis the shift in political scenery may have significantly altered the risk exposition of Brazilian firms that negotiate their shares on the São Paulo Stock Exchange (BM&FBOVESPA). From the perspective of discontinuity regression, this paper aims to shed light on the impeachment effects to the risk exposition of Brazilian firms measured by Value at Risk, in turn, estimated via quantile regression models. With weekly information on 132 stocks, from 01/jan/2014 to 14/feb/2018, we have found evidence indicating the presence of significant effects - with confidence level of 5% - on the Value at Risk of these companies - most of them pointing a reduction on the risk measure - due to the steps of the process of impeachment, highlighting the high incidence of the sectors of electric energy and commerce. However, significant effects were observed in less than 20% of the total assets analyzed. Finally, the results further indicate the presence of anticipated effects, in particular refering to the impeachment.